Increased iron level in motor cortex of amyotrophic lateral sclerosis patients: An in vivo MR study. Issue 5 (September 2014) - Yu, Jixu; Qi, Faying; Wang, Nian; Gao, Peihong; Dai, Shouping; Lu, Yucheng; Su, Quanping; Du, Yifeng; Che, Fengyuan
Abstract Amyotrophic lateral sclerosis (ALS) is one of the most common neurodegenerative disorders, but no definite mechanism has been defined on the loss of motor neurons in ALS and currently no therapy can block its progression. Many lines of evidence indicate that there is a disorder of iron homeostasis in ALS, and thus we sought to test the iron level in ALS patients by susceptibility weighted imaging (SWI). Sixteen ALS patients and 16 healthy persons underwent brain scans using SWI with a 3T Siemens MR scanner. The red nucleus, substantia nigra, globus pallidus, putamen, the head of caudate nucleus, and motor cortex were measured in the filtered phase images and analysed for their SWI phase values as relative marker for iron content. We found that phase shift values were significantly higher in the motor cortex of ALS patients by SWI, indicating increased iron level in this area. In contrast, we found that there were no differences of phase shift values between ALS patients and healthy controls in the other nuclei including the red nucleus, substantia nigra, globus pallidus, putamen and the head of the caudate nucleus. Furthermore, we found that there were no relationships between SWI signal and some clinical features of ALS. In conclusion, these results demonstrate that iron level increases in the motor cortex of ALS and that SWI is a reliable method to test iron in the brain.